Measuring investor intentions in Malaysia: A pilot study on robo-advisors among Millennials and Gen Z - Abdul Manaf, Suhaily Maizan; Ismail, Mohd Khairu Amin; Zakaria, Shahsuzan (Journal of Islamic, Social, Economics and Development, 2025)
Robo-advisors, a recent innovation in financial technology, are still emerging in the Malaysian market, primarily targeting millennials and Gen Z. However, the problem of decreasing engagement in using robo-advisors as an alternative source of investment has still been debated recently. This study explores factors influencing the intention to use robo-advisors through a pilot test to evaluate the usability and reliability of the survey questionnaire. Using a quantitative approach, data were collected via an online survey distributed through WhatsApp, Telegram, and Facebook to potential investors in Malaysia aged 18 to 45. A purposive sampling method was employed, and 30 completed questionnaires were analyzed. The pilot study assessed indicator reliability, internal consistency reliability, and convergent validity. Results revealed loadings ranging from 0.627 to 0.967, composite reliability indices from 0.903 to 0.976, and Average Variance Extracted (AVE) values between 0.613 and 0.873, confirming the constructs’ reliability. These findings suggest that the questionnaire is suitable for larger-scale research. This preliminary study offers insights to refine the questionnaire content for future investigations and provides an initial understanding of the factors shaping the intention to use robo-advisors in Malaysia. It also highlights the potential of robo-advisors to influence the country’s financial technology sector.